Research on the Development of School-based Curriculum for Gender Education for Students - Niu, Chunguang (Journal of Theory and Practice of Contemporary Education, 2023)
Gender education runs through the entire process from preschool education to higher education, deeply influencing the formation of students' worldviews, life views, values, and family views, and is related to students' career, family, and life happiness. This article introduces the implementation of school-based curriculum for gender education for normal university students in three aspects: curriculum design, curriculum implementation, and curriculum evaluation, and conducts in-depth discussions based on the implementation of the curriculum.